2019
DOI: 10.1021/acs.est.8b06389
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Reliability of Measuring Mercury Cycling Gene Abundance with Correlations with Mercury and Methylmercury Concentrations

Abstract: Methylmercury (MeHg) is a bioaccumulative toxic contaminant in many ecosystems, but factors governing its production are poorly understood. Recent work has shown that the anaerobic microbial conversion of mercury (Hg) to MeHg requires the Hg-methylation genes hgcAB and that these genes can be used as biomarkers in PCR-based estimators of Hg-methylator abundance. In an effort to determine reliable methods for assessing hgcA abundance and diversity and linking them to MeHg concentrations, multiple approaches wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 95 publications
4
98
0
Order By: Relevance
“…We still know relatively little about the distribution of Hg-methylating organisms in the environment, although the discovery of the hgcAB gene pair conferring Hg-methylation capability has greatly improved their identification (Parks et al, 2013;Bravo and Cosio, 2019). Mercury methylation is a species (and possibly strain)-specific trait that is not well predicted by 16S rRNA taxonomic classification (Ranchou-Peyruse et al, 2009;Gilmour et al, 2013;Yu et al, 2013;Gilmour et al, 2018;Christensen et al, 2019). The presence or abundance of groups of microbes that include Hg methylators is not predictive of the abundance of hgcAB + microbes.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We still know relatively little about the distribution of Hg-methylating organisms in the environment, although the discovery of the hgcAB gene pair conferring Hg-methylation capability has greatly improved their identification (Parks et al, 2013;Bravo and Cosio, 2019). Mercury methylation is a species (and possibly strain)-specific trait that is not well predicted by 16S rRNA taxonomic classification (Ranchou-Peyruse et al, 2009;Gilmour et al, 2013;Yu et al, 2013;Gilmour et al, 2018;Christensen et al, 2019). The presence or abundance of groups of microbes that include Hg methylators is not predictive of the abundance of hgcAB + microbes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the Hg-methylators confirmed in culture, sulfate-and iron-reducing Deltaproteobacteria, acetogenic and syntrophic Firmicutes, and methanogenic Archaea (Compeau and Bartha, 1985;Fleming et al, 2006;Kerin et al, 2006;Ranchou-Peyruse et al, 2009;Gilmour et al, 2013;Yu et al, 2013;Gilmour et al, 2018;Goñi-Urriza et al, 2019)genomic analyses have identified hgcAB (and thus inferred the ability to produce MeHg) in many other lineages including Chloroflexi, Chrysiogenetes, Aminicenantes (Candidate Phylum OP8), Atribacteria (Candidate Phylum OP9), Nitrospira, Nitrospina, Elusimicrobia, Thermotogae and Spirochaetes (Podar et al, 2015a;Gionfriddo et al, 2016;Liu et al, 2018a;Bowman et al, 2019;Christensen et al, 2019;Jones et al, 2019). The occurrence of hgcAB in Bacterial and Archaeal genomes is rare but widely dispersed across phyla (Parks et al, 2013;Podar et al, 2015a;Jones et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations